Desing and analysis: a researchers handbook - Keppel, Geoffrey. 1935- (Prentice Hall, 1991)
Designed to bridge the gap between elementary books on statistics and experimental design and professional source books this volume provides students with the basic information to design and analyze meaningful experiments in the behavioural, social and biological sciences. It offers detailed coverage of the most common experimental designs used by behavioural scientists, showing the amount of information obtainable from varying designs.